Skin-to-skin contact—An effective intervention on pain and stress reduction in preterm infants - Pavlyshyn, Halyna; Sarapuk, Iryna (Frontiers in Pediatrics, 2023)
Introduction. The outcomes of pain and stress in preterm infants in the neonatal intensive care units (NICUs) compel the continued search for pain- and stress-reducing interventions. The objective of the study. To investigate how skin-to-skin contact (SSC) influences chronic pain and stress in preterm infants in the NICU. Materials and methods. The study included 140 preterm infants in the NICU with gestational age less than 34 weeks. The overall design was a baseline-response design. Urine and saliva were collected before (baseline) and after SSC to measure pain and stress markers by enzyme immunoassay method. The behavioral indicators of chronic pain were assessed using the EDIN (Échelle Douleur Inconfort Nouveau-Né – neonatal pain and discomfort). Results. There was a significant decrease in the dopamine level in preterm infants after SSC in comparison with baseline values (85.99 [69.35; 112.20] pg/ml vs 132.20 [104.80; 183.70] pg/ml), p˂0.001. The β-endorphin and serotonin levels increased after SSC (40.09 [26.81; 70.63] pg/ml vs 29.87 [20.61; 46.94] pg/ml, p=0.009 and 25.49 [20.45; 40.08] ng/ml vs 22.30 [15.13; 31.65] ng/ml, p=0.011, respectively). A significant decrease in cortisol levels in saliva and urine after SSC in comparison with baseline values (0.125 [0.079; 0.225] μg/dL vs 0.371 [0.188; 1.002] μg/dl, p=0.000 and 27.06 [14.59; 35.35] ng/ml vs 35.25 [19.78; 61.94] ng/ml, p=0.001, with a simultaneous increase of oxytocin level (57.00 [36.55; 88.49] pg/ml vs. 38.20 [28.78; 56.04] pg/ml, p=0.009 were revealed. The total pain EDIN score in infants after SSC was below 6 points, significantly decreasing compared to the baseline (p˂0.05). Conclusion. Preterm infants in the NICU experience stress and pain, which were confirmed by the EDIN pain scale and laboratory markers. The level of dopamine and cortisol as pain and stress hormones were reliably high, and normalized after regular SSC. Simultaneously, pain-relieving and anti-stress markers of oxytocin, β-endorphin and serotonin reliably increased in preterm infants in response to the SSC.